Spatial and temporal dynamics of the primate community in a regenerating forest of the Manu Biosphere Reserve, Peru - Mendoza-Soto, Jackeline Aida (2024)
Introduction: Amazonian forests with varying degrees of anthropogenic disturbance in the process of natural regeneration harbour many sympatric primate species. However, studies on their usage by primates are still lacking. Objective: To comprehensively study the spatial and temporal dynamics within the primate community in a regenerating forest within the Manu Biosphere Reserve. Methods: Two sets of historical data from Crees Foundation for Manu were analyzed, comprising records from January 2011 to February 2023 and corresponding to data obtained through incidental data and Terrestrial In-line Transects in three types of forest with different degrees of historical disturbance. Results: Lagothrix lagothricha and Ateles chamek showed a preference for less disturbed forests; Plecturocebus toppini, for more disturbed forests; and the other species did not show a clear preference. Regarding vertical stratification, A. chamek, L. lagothricha and Alouatta sara showed a preference for the upper stratum, P. toppini, Saimiri boliviensis and Sapajus macrocephalus showed a preference for the middle and upper strata and Leontocebus weddelli and Aotus nigriceps, for the middle stratum. According to the temporal activity of each species, seven species (A. chamek, S. macrocephalus, S. boliviensis, P. toppini, L. lagothricha, L. weddelli, and A. sara) were observed during the day, four were similar. Conclusions: The primate community varies according to disturbance gradient due to the preferences of some species. The recorded primates make a differentiated use of the vertical strata and most of them show diurnal activity.